2018
DOI: 10.1111/jfpp.13573
|View full text |Cite
|
Sign up to set email alerts
|

Orthodox tea (Camellia sinensis L .) oxidation under the influence of compressed air: Process optimization

Abstract: Oxidation of the hand‐rolled tea leaves (Camellia sinensis) was done by subjecting the leaves to an oxygen‐enriched environment, under the influence of compressed air. Different air pressure (101–303 kPa) and time (0–90 min) combinations were formulated (central composite design) for the experimental runs. A two‐phase analysis was conducted to determine the responses for pre‐drying samples (theaflavin, thearubigins, and total color of the oxidized tea leaves) and post‐drying samples (aroma index, lightness, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…(a–c). The change in the TR values at atmospheric oxidation is consistent with previous studies, which also suggested an increasing trend. At an elevated oxygen concentration inside the SOC, the rate of increase in %TR was faster, as observed in Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…(a–c). The change in the TR values at atmospheric oxidation is consistent with previous studies, which also suggested an increasing trend. At an elevated oxygen concentration inside the SOC, the rate of increase in %TR was faster, as observed in Fig.…”
Section: Resultssupporting
confidence: 92%
“…5(b). The TF values of oxidized samples in the SOC are fairly close to the reported values 21 obtained from an environmental control chamber, without the aid of a humidifier and air blower. The optimum oxidation duration is decided based on the peak TF value.…”
Section: Performance Validation Of Soc Observed Quality Parameters Frsupporting
confidence: 84%
See 3 more Smart Citations